+CANINE ATOPIC DERMATITIS: DETAILED GUIDELINES FOR DIAGNOSIS AND ALLERGEN IDENTIFICATION - Coutinho, Diogenes José Gusmão; Souza, Jaqueline Saraiva de; Silva, Jaqueline Moura da; Teixeira, Ana Paula (Revista Ibero-Americana de Humanidades, Ciências e Educação, 2023)
Canine atopic dermatitis (AD) is a common, genetically predisposed, inflammatory and pruritic skin disease. The variation in clinical presentations, due to genetic factors, extent of the lesions, stage of the disease, secondary infections, as well as resemblance to other non-atopic related skin diseases, can complicate a diagnosis of canine AD. A sub-group of the International Committee for Allergic Diseases in Animals (ICADA) was tasked with the development of a set of practical guidelines that can be used to assist practitioners and researchers in the diagnosis of canine AD. Online citation databases and abstracts from international meetings were searched for publications related to the topic, and combined with expert opinion where necessary. The final set of guidelines was approved by the entire committee.